Exam ref 70-762 developing SQL databases - Davidson, Louis (Microsoft Press, 2017)
Prepare for Microsoft Exam 70-762, Developing SQL Databases -and help demonstrate your real-world mastery of skills for building and implementing databases across organizations. Designed for database professionals who build and implement databases across organizations and who ensure high levels of data availability, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the MCSA level. Focus on the expertise measured by these objectives: Design and implement database objects Implement programmability objects Manage database concurrency Optimize database objects and SQL infrastructure This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes you have working knowledge of Microsoft Windows, Transact-SQL, and relational databases About the Exam Exam 70-762 focuses on skills and knowledge for building and implementing databases across organizations and ensuring high levels of data availability. About Microsoft Certification Passing this exam earns you credit toward a Microsoft Certified Solutions Associate (MCSA) certification that demonstrates your mastery of modern database development. Exam 70-761 (Querying Data with Transact-SQL) is also required for MCSA: SQL 2016 Database Development. See full details at: microsoft.com/learning.
Includes index. - Online resource; title from title page (Safari, viewed January 27, 2017)
Keywords: SQL server; Client/server computing; Database management; Architecture client-serveur (Informatique); Bases de données; Gestion; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference